Analisis Pemanfaatan Sistem APG X Atas Sistem Pembayaran Jasa Tenaga Kerja Bongkar Muat Pupuk Pada PT. Pupuk Sriwidjaja Palembang - Ulfa, Sapuro; Khairani, Siti (Jurnal Akuntansi dan Keuangan, 2025)
This  research  is a  qualitative  research  that  aims  to  find  out  how the payment system for fertilizer loading and unloading labor (TKBM) services after the use of the APG X system and the impact of the APG X system  on the payment system for fertilizer TKBM services at PT Pupuk Sriwidjaja Palembang. Data  collection  techniques through observation and interviews. The  results  showed that at the beginning of the implementation process of APG X system utilization at PT. Pusri Palembang there are technical and social challenges where social challenges there  are  still  differences  in  vendor  perceptions in using the APG X system, especially vendors in the East Java region and new vendors and technical challenges need to be developed on the APG X system to make it easier for vendors to use the APG X system without further data processing, besides  that the utilization of the APG X system has a positive impact on the payment of fertilizer TKBM services to vendors of PT Pusri Palembang where vendors are faster in billing because of the ease of completing billing documents, preventing the potential for double billing by vendors and a good impact on the vendor's cash flow because it is faster to receive payment for fertilizer TKBM services.